2004
DOI: 10.1111/j.1471-0528.2004.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Spousal physical violence against women during pregnancy

Abstract: Objective To determine the prevalence of physical violence during pregnancy and the factors associated with it.Design A population-based, multicentre, cross sectional household survey.Setting Rural, slum and urban non-slum areas of Bhopal, Chennai, Delhi, Lucknow, Nagpur, Trivandrum and Vellore, in India. Participants A total of 9938 women who were 15 to 49 years of age and living with a child younger than 18 years old. Methods Probability proportionate to size sampling of households was performed in three str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
91
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 24 publications
7
91
2
Order By: Relevance
“…From various studies worldwide, incidence of domestic violence during pregnancy is between 8 to 15%. [7][8][9][10] However, these figures represent only the tip of the iceberg. There is gross underreporting of cases of domestic violence.…”
Section: Discussionmentioning
confidence: 99%
“…From various studies worldwide, incidence of domestic violence during pregnancy is between 8 to 15%. [7][8][9][10] However, these figures represent only the tip of the iceberg. There is gross underreporting of cases of domestic violence.…”
Section: Discussionmentioning
confidence: 99%
“…In India suspected infidelity, use of alcohol in the partner, dowry harassment and low education are factors associated with partner violence (73).…”
Section: Factors Associated With Intimate Partner Violence During Prementioning
confidence: 99%
“…[1][2][3][4] In a study from India, moderate to severe spousal physical violence during pregnancy was 13%. [5] Most of the studies have shown spousal or intimate partner violence as the main focus of domestic violence. However, in North India we expected a different pattern, i.e.…”
Section: Introductionmentioning
confidence: 99%